ON CERTAIN TOPOLOGICAL STRUCTURES OF 2- NORMED SPACE VALUED ORLICZ SPACE ï€ c0 ((S, ||.,.||), Î¦, uâ€“ ) OF NULL SEQUENCES - Pahari, Narayan Prasad (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
The aim of this paper is toÂ Â introduceÂ Â and studyÂ a newÂ classÂ Â c0 (( S, ||. , .||), F , ) Â Â Â Â of 2-normed spaceÂ valued vector sequences using Orlicz function as a generalization of the basic space c0 Â ofÂ allÂ converging Â sequences. Beside theÂ investigation pertaining toÂ the Â linear space Â structures ofÂ the classÂ c0 (( S, ||. , .||), F , ) Â with some Â topological properties, our primarily interest is to explore the containment relationÂ ofÂ the classÂ c0 (( S, ||. , .||), F , ) Â in terms of different values of Â . Â Keywords: Sequence space, Normal Space , 2- normed Space, Orlicz Function, Orlicz Space. Â 2010 AMS Subject Classification: Primary - 46A45, Secondary - 46B 15Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â